TumorMet: A repository of tumor metabolic networks derived from context-specific Genome-Scale Metabolic Models - Ilaria Granata; Ichcha Manipur; Maurizio Giordano; Lucia Maddalena; Mario Rosario Guarracino (Scientific Data, 2022)
Measurement(s) gene expression, metabolic relationships Technology Type(s) Genome Scale Metabolic Models; Computational network biology Sample Characteristic - Organism Homo sapiens